DAKWAH MELALUI YOUTUBE (ANALISIS PESAN DAKWAH USTADZ HANAN ATTAKI) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
The purpose of this research is to obtain information about Ustadz Hanan Attaki's da'wah messages on the Hanan Attaki Youtube channel. In addition, the researcher also wanted to know the method of delivering the da'wah of Ustadz Hanan Attaki on the Hanan Attaki Youtube channel to students of the Department of Communication and Islamic Broadcasting, Faculty of Da'wah and Communication UIN Alauddin Makassar. The results showed that;  The message of the da'wah conveyed by Ustadz Hanan Attaki contained motivations, suggestions, warnings which were packaged in a video spiced up in choosing dictionaries that were adaptive to the Madame so that it could be easily accepted and understood by the Madame. The method of delivering Ustadz Hanan Attaki's da'wah has characteristic audio and visual sound that is compatible with the way of delivering his preaching and with various themes each week. Likewise with the title of the preaching content that keeps millennial young people motivated.